Uterus transplantation: ethical and regulatory challenges - Arora, Kavita Shah (Journal of medical ethics, 2014)
Moving forward rapidly in the clinical research phase, uterus transplantation may be a future treatment option for women with uterine factor infertility, which accounts for three per cent of all infertility in women. This new method of treatment would allow women, who currently rely on gestational surrogacy or adoption, to gestate and birth their own genetic offspring. Since uterus transplantation carries significant risk when compared with surrogacy and adoption as well as when compared with other organ transplants, it requires greater justification because its goals are quality of life, not life-saving, in their scope. It is important to address questions regarding the physical, psychosocial and ethical risks and benefits of uterus transplantation for all three parties involved—the patient, the donor and the potential child—as well as discuss the regulatory implications as research on uterus transplantations moves forward.